NUMERICAL MODELLING AND SIMULATION OF BONE DRILLING TO MINIMIZE BONE NECROSIS BY CONTROLLING HEAT GENERATIONS - MOHD MOKHTAR, MUNAIBAH (2013)
Bone drilling method is one of the medical approaches to handle fracture in trauma injury. It involves the insertion of a screw and/or a plate for temporary support. However, drilling generates heat thus causing thermal necrosis. The temperature which reach above thermal necrosis threshold during drilling causes two problems; the bone tissue losses its regeneration ability and loosening of the surgical fixation over time. This project aims to develop appropriate numerical heat transfer model adaptation of the heat source approach for bone drilling with the purpose of minimizing thermal necrosis. Method of investigations used were numerical modeling and simulation using ANSYS parametric design language (apdl). The relationship of drill speed, feed rate, point angle, helix angle and drill bit diameter were investigated using the heat source model. Prediction of the temperature distribution and a parametric study was conducted.